IoT-Based Server Room Temperature and Humidity Monitoring - Asti Triwulanda (Jurnal Jaringan Komputer dan Keamanan, 2025)
Monitoring the environmental conditions of server rooms is essential to ensuring optimal hardware performance, maintaining system reliability, and preventing device failure. This study proposes an Internet of Things (IoT)-based monitoring system for temperature and humidity control using a NodeMCU ESP8266 microcontroller combined with a DHT22 sensor. The system measures environmental conditions in real time and transmits the collected data over a Wi-Fi network to the Blynk platform for visualization and remote monitoring. Alerts are generated when temperature or humidity exceeds predefined thresholds, enabling preventive action to avoid equipment damage. The implementation demonstrated that the system effectively monitors server-room environmental parameters, provides accurate and real-time data visualization, and enhances the overall management of server-room conditions.